A service composition platform in cloud computing using mobile devices for smart shopping - Tsongoro, Lavender (Department of Electrical Engineering, 2017)
The development of the Next Generation Networks (NGN) such as LTE, WiMax and 5G networks has resulted in the development of more diverse mobile services. Many voice and video services have been developed (e.g. Viber, Skype and WhatsApp). Social networking sites have also been developed (e.g. Facebook, Instagram and Twitter). Users of these services are increasingly expecting and demanding more complex services which have more capabilities that can improve their day to day business. Users want services that are reliable, fast and easy to use. To effectively design and implement services, Service Oriented Architecture (SOA) principles are useful and some of the advantages of designing services using SOA principles are: • Improved interoperability; • Cross platform and cross application integration; • Reusability; • Service composition. Service composition has the advantage that customized services with more features can be developed by combining two or more basic services. In this research, SOA principles are used to design a cloud based Mobile Smart Shopping Service Platform. Canal Walk Shopping Mall, which is located in Cape Town, South Africa is used as a case study. Various mobile services are composed in order to solve the problem of getting information about the services provided by the shopping mall and also to show the available parking bays, which has become a major concern due to the rapid growth of the surrounding residential and business areas. Performance measurements for the Smart Shopping service are then conducted to test its power consumption, memory usage, bandwidth usage and application timeline. Conclusions are drawn and recommendations for possible future development are then provided.